Effective PAPR reduction in SCFDM-based massive MIMO system using binary crow search algorithm for visible light communication towards 5G networks - Sindhuja, Rajesh; Shankar, Arathi R (IET communications, 2020)
Presently, the single-carrier frequency division multiplexing (SCFDM)-based visible light communication (VLC) system is extensively implemented for secure and high-speed data transmission. However, the effect of additive white Gaussian noise in VLC with white light-emitting diode is high, due to a high peak to average power ratio (PAPR). To address this difficulty in 5G networks, two objectives were carried out in this research article. Initially, selective mapping (SLM) scheme was applied for PAPR reduction, because it considerably selects the effective phase rotation factors that help in the reduction of system complexity. Besides, binary crow search algorithm was used for sub-block partition optimisation in SLM for enhancing the convergence speed of the proposed SCFDM-based VLC system. In the experimental investigation, the proposed SCFDM-based VLC system was analysed in terms of complementary cumulative distribution function, bit error rate and signal-to-noise ratio by varying the equalisation techniques for 5G networks.